Resource management: Fragmentation of land ownership and its impact on sustainability of agriculture - Khalid, Haniza; Yusuf, Muhammad Dayyan (2012)
The inevitable implications of fragmenting farmland ownership are (i) uneconomic land sizes and farm operations, (ii) greater tendency to convert the farmland to other uses (and hence, the subsequent decline of food production capabilities of the country as a whole) and (iii) under-investment in the land as co-owners disagree on how land should be utilized. Fragmentation of ownership occurs in two ways, one is through the practice of distributing a deceased’s assets based on the literal application of the Fara’id calculations. Another is through formal and informal credit arrangements using land as a form of collateral. The implications of land fragmentation go against the government efforts to revitalize agriculture for trade and food security objectives. This paper evaluates land fragmentation problem in Malaysia and suggests policy-improvement measures that can be adopted by the present land resource management authorities.